Amery Ice Shelf surface snowmelt detected by ASCAT and Sentinel-1. Issue 5 (4th May 2019) - Zhou, Chunxia; Zheng, Lei; Sun, Qizhen; Liu, Ruixi
ABSTRACT: Widespread movement of meltwater has been found on the Amery Ice Shelf (AIS). Intensive surface snowmelt could accelerate ice loss and endanger the ice shelves under climate warming. In this study, the Advanced Scatterometer (ASCAT) was used to study the detailed melt patterns on the AIS, which was confirmed by the wet snow mapped by Sentinel-1 Synthetic Aperture Radar (SAR) images with a much higher spatial resolution. Melt seasons were longer than 50 days in the eastern part of AIS. Conversely, a large proportion of the western AIS only melted occasionally for several days with the exception of blue ice areas. Two obvious snowmelt patterns are found on the AIS. First, the opposing summer katabatic wind directions on the eastern and western sides of the AIS result in a warmer eastern AIS compared with the western side, which leads to the expansion of snowmelt from east to west on the AIS. Second, intense snowmelt was found in the grounding zone with low-albedo blue ice and rock outcrops. However, ASCAT fails to detect snowmelt in these places due to the dominated surface radar scattering. AIS melt patterns are determined by both meteorological conditions and the underlying surface.